(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aims to know the problems faced by the families of disabled children, and the ability of these families to handle such problems. The area of south Amman was chosen, and 30 families from this area was chosen randomly, and a questionnaire was designed to be answered by the father and mother, which include two sections, one for the problems faced daily , and other for how and the ability of handling these problems. The results showed that most frequent problems faced was first helping the child with his daily needs, second the need for the family to organize its day, and then financial problems. For handling the problems, anger and stress was the most frequent because of problems relating to society and dealing with others. Other results was that financial problems and transportation problems leads for family cooperation. The results showed that there are many problems related to having disabled child in the family , some of these problems the family can handle and some cause serious problems for the family and it can’t be handled. تهدف الدراسة إلى التعرف على المشكلات التي تؤثر على عائلة الأطفال من ذوي الحاجات الخاصة , وكيفية التعامل معها ومقدرة هذه العائلات على التعامل مع هذه المشكلات . تم اختيار منطقة جنوب عمان لتكون مجتمع البحث وتم اختيار 30 عائلة بشكل عشوائي من الأسر التي لديها أطفال من ذوي الاحتياجات الخاصة تدرجت من الإعاقات الجسدية البسيطة إلى الإعاقات العقلية الكاملة أو الجزئية, وتم عمل إستبانة ليتم الإجابة عليها من قبل الأب والأم في كل عائلة واشتملت الاستبانة على محورين هما محور المشكلات ومحور التعامل مع المشكلات الناتجة عن وجود طفل من ذوي الاحتياجات. أظهرت النتائج أن المشكلات الرئيسية التي تواجه العائلات هي مشاكل في مساعدة الطفل بشكل يومي, ومن ثم مشاكل تنظيم العائلة ليومها العادي ويليها مشاكل مالية. بالنسبة لمقدرة العائلة لحل المشكلات فكان التوتر والغضب موجودا بسبب مشاكل أهمها المشكلات المتعلقة بالمجتمع والتعامل مع الآخرين, فيما كانت المشكلات المالية ومشاكل التنقل تؤدي إلى تعاون الأسرة مع بعضها لتخطي هذه المشكلات. أظهرت الدراسة أن العائلة الأردنية تعاني من مشاكل عدة لوجود الأطفال ذوي الحاجات الخاصة , لكنها تستطيع التكيف مع بعض المشكلات ,في حين أن بعض المشكلات الأخرى تؤدي إلى ضعف في التأقلم والى عدم قدرة على التعامل معها.